A Study on the Applications of Synthetic Zeolites: Unleashing the Full Potential of Synthetic Zeolites through Detailed Mineralogical Characterization (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Zeolites and zeolite rocks are commonly used in different industrial applications. Synthetic zeolites present an attractive material for environmental applications because of their high abundance, availability and low costs. Depending on geological settings and conditions during mineral formation, Synthetic zeolite deposits usually represent a heterogeneous mixture of zeolite minerals together with varying amounts of gangue minerals (e. g. quartz, feldspars and phyllosilicates). Hence, profound mineralogical knowledge and a detailed characterization of Synthetic zeolites are essential for tapping their full potential in any practical application. However, this is rarely done as detailed mineralogical characterizations are elaborate and often neglected in favour of bulk chemical analyses (e. g. XRF).